Etika profesi dalam perusahaan jasa sub sektor hotel - Diana, Wahyu; Yanuar Ramadhan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The interaction between humans and the environment has a set of norms and ethics that must be followed to avoid sanctions. Ethics seems to minimize behavior that harms each other when socializing. The purpose of this study is to find out if any employees at Favehotel Jakarta are fully committed to ethics and morals to support maximum service to service users. This research method is performed using qualitative methods in the form of information and descriptive analysis related to the problem being run, and clearly talks about the relevant problem and the data obtained through observation. The results of the survey show that the importance of professional ethics in all sectors of the service industry is to maintain the operational quality of guests and to maintain the smooth operation of services. The next interesting study to be developed as a study is the professional ethics of the hospitality industry.